A methods engineering study of FunFarm Concepts, Inc. - Enriquez, Norman (College of Engineering, 1994)
The group conducted a study on FUNFARM CONCEPTS, INC., a company involved with the production of stuffed toys and other novelty items. The said company is presently undergoing an expansion process, merging together the two sites it has presently--one containing the sampling, cutting and sewing departments, the other one containing the stuffing and finishing departments. The new site is still in the process of construction. Our study is considered timely because our recommendations may be useful in the new set up of the company. Of the five departments of the company, the group decided to concentrate on the stuffing department. After careful study, we decided that the stuffing department is the bottleneck of the production process. Much of the inputs from the sewing department is stored in the stuffing department because of lack of manpower and lack of standard procedure of stuffing. We conducted a predetermined time study to come up with a standard time for stuffing. With this proposed time, stuffing time was reduced from 13.5 minutes to 9.0 minutes. The construction of tables and chairs help reduce the stuffing time. The proposed table is suitable for the stuffing process, since all the materials that might be needed by a worker are within hands reach. Little body movement is now involved. A worker also has a more suitable and convenient chair. There is more ease in the stuffing process. The standardization of time is also a good check of the performance of a worker. Knowing that it takes only an average of 9.09 minutes to complete a stuffed toy, the supervisor knows just how much to expect from each worker at the end of the day. Efficiency will thus be encouraged. A study of the forms of the company was also conducted. At present, there is only one form used by the department, the tally sheet. The rest of the forms are just written on yellow paper, or any other paper for that matter. The group recommended the addition of another form to check on the entering and leaving physical quantities. (The proposed form may also be used by the sewing department.) Also, we decided to clearly define the task of the supervisor. More than just an ordinary worker, the supervisor is now tasked with the checking/control of the trilobals stuffed during each workday. The supervisor compares the tally sheets submitted to him/her by the workers with the actual number of finished products. He/She then submits the tally sheets to the secretary for filing. The supervisor must regularly check on the performance of his/her workers. With these recommendations, the group feels that the company's productivity and efficiency will thus be increased.